2021
DOI: 10.1371/journal.pone.0254652
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 influences on US recreational angler behavior

Abstract: Recreational angling in the United States (US) is largely a personal hobby that scales up to a multibillion-dollar economic activity. Given dramatic changes to personal decisions and behaviors resulting from the COVID-19 pandemic, we surveyed recreational anglers across the US to understand how the pandemic may have affected their fishing motivations and subsequent activities. Nearly a quarter million anglers from 10 US states were invited to participate in the survey, and almost 18,000 responded. Anglers repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 26 publications
(30 reference statements)
4
47
2
Order By: Relevance
“…Additionally, recreation has a positive effect on neutralizing other pandemic effects, such as weight gain, e.g., [ 8 , 9 , 10 ]. As can be seen from this and other studies, e.g., [ 21 ], angling can be viewed as an activity that can significantly reduce the negative social and psychological impacts of pandemics.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Additionally, recreation has a positive effect on neutralizing other pandemic effects, such as weight gain, e.g., [ 8 , 9 , 10 ]. As can be seen from this and other studies, e.g., [ 21 ], angling can be viewed as an activity that can significantly reduce the negative social and psychological impacts of pandemics.…”
Section: Discussionmentioning
confidence: 52%
“…One of the most important issues in this matter is the perception of angling as a safe form of recreation during a pandemic. Recent studies, e.g., [ 21 , 23 ], as well as this paper, have indicated that anglers perceive their hobby as a safe activity. Almost 98% were not afraid of getting sick during fishing, while two-thirds (66.5%) were not afraid of getting sick at all.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations